Coordinated information retrieval for building contractors' tendering - Betts, Martin Peter (Department of Construction Economics and Management, 2026)
This thesis represents the results of a progranune of research investigating the problem of the coordination of data used in the preparation of tenders for construction projects by building contractors. The approach is one of using data modelling techniques to produce a relational database as a dynamic store whereby all data used and produced by tasks of tendering can be inter-related in a single source. The database is tested for its ability to manipulate data from a construction project to enable retrieval of data for individual tasks in an interrogative form. Interrogations or retrievals from the database are assessed for their flexibility in terms of the content and level of detail of what has been quantified and the format or structure of data presentation. This flexibility is compared with that attainable through current alternative methods.